Measuring the Costs of Value Stream by using the Supply Chain Management and its Role in Cost Management - Hani Al-Zameli, Ali Abdul-Hussein; Al-Sfan, Maytham Badr Bawie; Ojah, Hassnain Kadhim (ExcelingTech, 2019)
The present research aims at studying the knowledge bases of value stream costs, Lean Accounting and supply chain management. Proper supply chain performance plays a crucial role in the success of organizations. Therefore, it is essential to use an appropriate supply chain performance assessment system to continuously improve it. The purpose of this research is to analyze supply chain performance according to the operational reference model of supply chain. In addition to using the tools of Lean Accounting in measuring the costs of value stream so that helps economic units in managing and reducing costs consistent with the requirements of the modern manufacturing environment. The measurement of value steam costs helps to provide appropriate information that can serve the management of the economic unit in decision making process in such a way as to help control all elements of the value steam costs effectively and efficiently. As well as improving and developing value stream reports as a result of the easy understanding of the stream of information and the stream of materials, assets and procedures in a streamlined. The current research has been applied in Al-Zawraa General Company/Power Structured Factory for financial year ended 2017. The research also presented a set of recommendations that emphasize the importance of using Lean Accounting tools in measuring costs of value stream in the manner that is reflected in cost management effectively and efficiently.